Reinforced magnesium base plate and composite plate with reinforced magnesium base plate
By using reinforced magnesium substrates prepared with specific proportions of magnesium oxide, wood fiber and other components, the problems of deformation and early strength of existing building boards in humid environments are solved, and the early strength improvement and moisture resistance of composite boards are achieved , meets the needs of decoration stability and durability.
Patent Information
- Application Number
- CN202411572786.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
AI Technical Summary
Existing building panels such as ceramic tiles, stone and glass magnesium flat plates are prone to deform when they are in dark and humid environments for a long time, and have a long maintenance cycle and low early strength, making it difficult to meet the needs of decoration stability and durability.
A reinforced magnesium substrate is adopted, which consists of magnesium oxide, ligno fibers, citric acid, phosphoric acid, sodium sulfate and magnesium sulfate. By controlling the proportion of these components, a gelled material with good early strength and moisture resistance characteristics are formed. The reinforced magnesium substrate can be used to prepare composite panels, and the stability and durability of composite panels are further improved by providing wooden panels and wear-resistant layers on both sides.
It has achieved early strength improvement and moisture resistance improvement of the magnesium substrate, reduced deformation of the board in humid environment, extended the maintenance cycle, and improved the overall decorative stability and durability.
Smart Images

Figure CN119409476A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building boards, and in particular relates to a reinforced magnesium base plate and a composite board with the reinforced magnesium base plate. Background Art
[0002] In the field of building boards, boards laid on the ground or walls usually have the characteristics of waterproofness, moisture resistance, low cost, and not easy to deform. In this regard, the market mostly uses laminated floors of fiberboard or particle board, or hard materials such as tiles and stones. According to different needs of users, wood boards, plastic boards, hard boards, etc. are selected to be laid on the floor or wall.
[0003] When users use hard materials such as tiles and stones, although the materials themselves have the characteristics of beautifying objects, being easy to wipe, and not being corroded by dust and filth, they are hard and tough, and can withstand less external deformation. If tiles and stones are subjected to external stress, they will crack or break. Therefore, when installing tiles and stones on walls or floors, they are usually laid manually and bonded with adhesives, cement, etc., and there is no additional structure for fixing the tiles and stones after or during cutting.
[0004] Some users use common glass magnesium flat panels instead of tiles and stones. Glass magnesium flat panels are also called fireproof composite panels and magnesium oxide panels. They are magnesium oxide, magnesium chloride and water ternary systems, which are configured and modified by adding modifiers to form a stable magnesium gelling material, with medium alkaline glass fiber mesh as a reinforcing material and lightweight materials as fillers. Although glass magnesium flat panels have good fire resistance, certain strength and waterproof and moisture-proof capabilities, correspondingly, when they are in a dark and humid environment for a long time, glass magnesium flat panels will deform greatly, affecting the stability of decoration; in addition, the maintenance period of glass magnesium flat panels is relatively long, and the early strength is low. Summary of the invention
[0005] According to various embodiments of the present application, a reinforced magnesium substrate and a composite panel having the reinforced magnesium substrate are provided.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A reinforced magnesium substrate comprises the following components in parts by weight: 240-280 parts of magnesium oxide, 172-192 parts of wood fiber, 1.3-3.5 parts of citric acid, 1.3-3.5 parts of phosphoric acid, 1.3-3.5 parts of sodium sulfate, 90-120 parts of magnesium sulfate, and 109-130 parts of water.
[0008] Optionally, the weight ratio of citric acid, phosphoric acid and sodium sulfate is 1:1:1.
[0009] Optionally, the weight portion of the magnesium oxide is 255-265 parts; the weight portion of the magnesium sulfate is 100-110 parts; and the weight portion of the water is 115-125 parts.
[0010] Optionally, the fiber length of the wood fiber is 3-6 mm, and the moisture content of the wood fiber is 0.5%-10%.
[0011] Optionally, the magnesium oxide is light-burned magnesium oxide, and the magnesium sulfate is anhydrous magnesium sulfate.
[0012] A composite panel with a reinforced magnesium substrate as described in the above solution, comprising:
[0013] A reinforced magnesium substrate configured as a sheet core of the composite panel;
[0014] The wooden board layer is arranged on both sides of the reinforced magnesium base plate and fixed relatively to the reinforced magnesium base plate;
[0015] The wear-resistant layer is arranged on the wooden board layer located outside the reinforced magnesium base plate and is relatively fixed to the wooden board layer.
[0016] Optionally, the composite board further includes a connecting layer, wherein the connecting layer is disposed between the wood board layer and the reinforced magnesium substrate, and the connecting layer is a polyurethane adhesive.
[0017] Optionally, the composite board further comprises decorative paper, wherein the decorative paper is arranged between the wood board layer and the wear-resistant layer.
[0018] Optionally, the composite board further comprises balancing paper, wherein the balancing paper is arranged on the wood board layer located on the inner side of the reinforced magnesium base plate, and the balancing paper faces the proximal end of the ground or wall on which the composite board is laid.
[0019] Optionally, the composite board further comprises a cushion layer, wherein the cushion layer is in contact with the ground or wall on which the composite board is laid.
[0020] Details of one or more embodiments of the present application are set forth in the following drawings and description. Features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a schematic structural diagram of a composite plate in one embodiment of the present invention;
[0022] Figure 2 is a schematic structural diagram of a composite plate in another embodiment of the present invention;
[0023] Figure 3 is a schematic structural diagram of a composite plate in another embodiment of the present invention;
[0024] Figure 4is a schematic structural diagram of a composite plate in another embodiment of the present invention;
[0025] Figure 5 It is a schematic structural diagram of a composite plate in another embodiment of the present invention.
[0026] In the figure: 1-reinforced magnesium substrate, 2-wooden board layer, 3-wear-resistant layer, 4-connecting layer, 5-decorative paper, 6-balance paper, 7-cushion layer. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The terms used in this disclosure are for the purpose of describing specific embodiments only and are not intended to limit the disclosure. The singular forms "a", "said" and "the" used in this disclosure and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0029] In the description of the present application, it should be understood that the terms "longitudinal", "lateral", "up", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0030] The present application relates to a reinforced magnesium substrate, comprising the following components in parts by weight: 240-280 parts of magnesium oxide, 172-192 parts of wood fiber, 1.3-3.5 parts of citric acid, 1.3-3.5 parts of phosphoric acid, 1.3-3.5 parts of sodium sulfate, 90-120 parts of magnesium sulfate, and 109-130 parts of water.
[0031] In one embodiment, the magnesium oxide is light-burned magnesium oxide, the magnesium content of the light-burned magnesium oxide is ≥85%, and the active magnesium content is >65%. Optionally, the weight portion of the magnesium oxide is 255-265 parts.
[0032] If the ratio of magnesium oxide to magnesium sulfate is further increased, the amount of mixing water will increase, the concentration of magnesium sulfate will be reduced, and water seepage may occur during material molding, affecting the coagulation efficiency and making it difficult to ensure good early strength; if the ratio of magnesium oxide to magnesium sulfate is reduced, although the concentration of magnesium sulfate is guaranteed, the gel material will have low mechanical properties and poor water resistance after molding, making it difficult to meet design requirements. If the amount of water relative to the sum of the mass of magnesium oxide and magnesium sulfate is increased, the concentration of magnesium sulfate will be reduced, and the problem of water seepage will still exist; if the amount of water is reduced, the mixture will not be completely hydrated, and the gelling material will not be easy to mold, affecting the mechanical properties of the material. Therefore, by controlling the ratio of magnesium oxide, magnesium sulfate and water, this embodiment can reduce the amount of water while ensuring that the mixture is completely hydrated, avoid water seepage and affect the coagulation of the material, and make the gelling material have good early strength after molding.
[0033] In one embodiment, the fiber length of the wood fiber is 3-6 mm, and the moisture content of the wood fiber is 0.5%-10%. Optionally, the weight of the wood fiber is 175-185 parts. The wood fiber can further improve the dispersibility of the cementitious material, making it evenly mixed with other components, and can also reduce the weight of the board to a certain extent and improve the structural strength.
[0034] In one embodiment, the weight portion of citric acid is 2-3 parts.
[0035] In one embodiment, the weight portion of phosphoric acid is 2-3 parts.
[0036] In one embodiment, the weight portion of sodium sulfate is 2-3 parts.
[0037] In one embodiment, the weight ratio of citric acid, phosphoric acid and sodium sulfate is 1:1:1. The synergistic combination of citric acid, phosphoric acid and sodium sulfate can achieve uniform and rapid hardening of the material. The specific ratio of citric acid, phosphoric acid and sodium sulfate can promote hydration reaction, accelerate the coagulation and hardening process, improve the early strength of the material, and control the pH value and electromotive force of the mixture to ensure uniform distribution of the cementitious material, thereby achieving uniform and rapid hardening.
[0038] In one embodiment, the magnesium sulfate is anhydrous magnesium sulfate. Optionally, the weight of the magnesium sulfate is 100-110 parts. Sodium sulfate can increase the swelling between wood fibers, thereby increasing the toughness of wood fibers, thereby improving the mechanical properties of the material.
[0039] In one embodiment, the weight parts of water is 115-125 parts.
[0040] The present application relates to a method for preparing a reinforced magnesium substrate, comprising the following steps:
[0041] A1. At room temperature, fully stir the components in a mixer according to the proportion to obtain a mixed slurry;
[0042] A2. Pour the mixed slurry into a mold and perform curing at a temperature of 20-30°C and a humidity of 40%-60%. After curing for 7 days, a reinforced magnesium substrate is obtained.
[0043] The present application will be illustrated by the following examples, but is not limited thereto.
[0044] (1) Raw material selection
[0045] The magnesium oxide is light-burned magnesium oxide, with a magnesium content of ≥85% and an active magnesium content of >65%. It was purchased from Yingkou Lixin Magnesium Industry Co., Ltd.
[0046] The wood fiber length was 5 mm, the moisture content was 0.5%-10%, and it was purchased from Wuxi Green Building Technology Co., Ltd.;
[0047] Citric acid with a purity of 99% was purchased from Huiyuan Environmental Protection Technology Co., Ltd.;
[0048] Phosphoric acid used was industrial grade 85% phosphoric acid purchased from Xiangyang Gaolong Phosphorus Chemical Industry;
[0049] Sodium sulfate with a purity of 99% was purchased from Zibo Huayan Chemical Co., Ltd.;
[0050] Magnesium sulfate was anhydrous magnesium sulfate purchased from Weifang Tianzhen Chemical Co., Ltd.
[0051] (2) Preparation method:
[0052] A1. At room temperature, fully stir the components in a mixer according to the proportion to obtain a mixed slurry;
[0053] A2. Pour the mixed slurry into a mold and perform curing at a temperature of 25°C and a humidity of 50%. After curing for 7 days, a reinforced magnesium substrate is obtained.
[0054] Experimental Example 1
[0055] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 2.38 parts of citric acid, 2.38 parts of phosphoric acid, 2.38 parts of sodium sulfate, 108 parts of magnesium sulfate, and 120 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, experimental sample 1 is obtained.
[0056] Experimental Example 2
[0057] First, take 245 parts of magnesium oxide, 175 parts of wood fiber, 2 parts of citric acid, 2 parts of phosphoric acid, 2 parts of sodium sulfate, 100 parts of magnesium sulfate, and 110 parts of water in a blender and stir them thoroughly to obtain a mixed slurry; then pour the mixed slurry into a mold and cure it at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, experimental sample 2 is obtained.
[0058] Experimental Example 3
[0059] First, 275 parts of magnesium oxide, 185 parts of wood fiber, 3 parts of citric acid, 3 parts of phosphoric acid, 3 parts of sodium sulfate, 115 parts of magnesium sulfate, and 130 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, experimental sample 3 is obtained.
[0060] Experimental Example 4
[0061] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 2.38 parts of citric acid, 2.38 parts of phosphoric acid, 2.38 parts of sodium sulfate, 95 parts of magnesium sulfate, and 110 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, experimental sample 4 is obtained.
[0062] Experimental Example 5
[0063] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 2.38 parts of citric acid, 2.38 parts of phosphoric acid, 2.38 parts of sodium sulfate, 118 parts of magnesium sulfate, and 125 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, Sample 5 is obtained.
[0064] Experimental Example 6
[0065] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 1.5 parts of citric acid, 3.5 parts of phosphoric acid, 2.5 parts of sodium sulfate, 108 parts of magnesium sulfate, and 120 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, experimental sample 6 is obtained.
[0066] Experimental Example 7
[0067] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 3.5 parts of citric acid, 1.5 parts of phosphoric acid, 2.5 parts of sodium sulfate, 108 parts of magnesium sulfate, and 120 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, experimental sample 7 is obtained.
[0068] Comparative Example 1
[0069] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 2.38 parts of citric acid, 2.38 parts of sodium sulfate, 108 parts of magnesium sulfate, and 120 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, a comparative sample 1 is obtained.
[0070] Comparative Example 2
[0071] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 2.38 parts of citric acid, 2.38 parts of phosphoric acid, 108 parts of magnesium sulfate, and 120 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, a comparative sample 2 is obtained.
[0072] Comparative Example 3
[0073] First, 260 parts of magnesium oxide, 180 parts of wood fiber, 2.38 parts of citric acid, 108 parts of magnesium sulfate, and 120 parts of water are fully stirred in a blender to obtain a mixed slurry; then the mixed slurry is poured into a mold and cured at a curing temperature of 25°C and a humidity of 50%. After curing for 7 days, comparative sample 3 is obtained.
[0074] The distribution ratios of each group of Experimental Examples 1-7 are shown in Table 1; the distribution ratios of each group of Comparative Examples 1-3 are shown in Table 2.
[0075] Table 1
[0076]
[0077]
[0078] Table 2
[0079] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Magnesium Oxide 260 260 260 Wood fiber 180 180 180 Citric Acid 2.38 2.38 2.38 Phosphoric acid / 2.38 / Sodium sulfate 2.38 / / Magnesium sulfate 108 108 108 water 120 120 120
[0080] The prepared experimental samples 1-7 and comparative samples 1-3 were tested using the following method, and the performance test results of each sample are shown in Table 3.
[0081] Compressive strength: tested in accordance with JC688-2006 "Glass Magnesium Flat Plate";
[0082] Impact strength: Refer to the impact strength determination method of GB / T1043.1 "Determination of impact properties of simply supported plastic beams Part 1: Non-instrumented impact test";
[0083] Anti-halogen reversion: Refer to JC688-2006 "Glass Magnesium Flat Plate", randomly cut one 200mm*200mm plate from each of the three plates of a group of samples, put them into a constant temperature and humidity box with a relative humidity greater than or equal to 90% and a temperature of 30℃-35℃, take them out after 24 hours and observe whether there are water droplets or moisture.
[0084] Table 3
[0085]
[0086] Comparison of the experimental examples and comparative examples shows that the flexural strength and impact strength of the experimental samples 1-7 are significantly improved, and the early strength after 7 days of curing is relatively high, close to the strength after continuing to cure for 14 days.
[0087] Continue to conduct shrinkage test on experimental samples 1-7 and comparative samples 1-3. The test method is as follows: measure the initial size of the board, place the board in a drying oven at 60°C, keep the temperature constant, take it out after 6 hours, record and measure the size of the board after continuous drying for 6 days and 10 days, and calculate the shrinkage rate according to the following formula:
[0088] Among them, L1 is the length after shrinkage; L0 is the initial length; W1 is the width after shrinkage; W0 is the initial length.
[0089] The test results of Experimental Examples 1-7 are shown in Table 4; the test results of Comparative Examples 1-3 are shown in Table 5:
[0090] Table 4
[0091]
[0092] Table 5
[0093]
[0094] From the measurement results in Table 4 and Table 5, it can be seen that the experimental samples 1-7 have excellent anti-shrinkage ability at high temperature, and still maintain good shrinkage resistance under the long-term test of 10 days.
[0095] The present application also relates to a composite panel with the reinforced magnesium substrate, such as Figure 1 As shown, it includes a reinforced magnesium substrate 1, a wood board layer 2 and a wear-resistant layer 3. The reinforced magnesium substrate 1 is used as the board core of the composite board and is arranged in the middle part of the composite board; the wood board layer 2 is arranged on both sides of the reinforced magnesium substrate 1 and fixed to the core board by an adhesive or other means; the wear-resistant layer 3 is arranged on the wood board layer 2 located outside the reinforced magnesium substrate 1 and is fixed thereto by an adhesive or other means, and the wear-resistant layer 3 faces the far end of the ground or wall where the composite board is laid.
[0096] Arranging the wooden board layer 2 on both sides of the reinforced magnesium substrate 1 can reduce the humidity expansion or contraction of the reinforced core, improve the stability of the composite board, and at the same time increase the overall strength and rigidity. The wooden board layer 2 can be a solid wooden board made of wood logs, or a solid wood particle board and other wood materials. Optionally, the wooden board layer 2 is a fireproof board with a thickness of not less than 0.5 mm.
[0097] Optionally, the reinforced magnesium substrate 1 , the wood board layer 2 and the wear-resistant layer 3 have the same size, and the reinforced magnesium substrate 1 , the wood board layer 2 and the wear-resistant layer 3 are all configured in a rectangular shape.
[0098] In one embodiment, if Figure 2 As shown, the wood board layer 2 and the reinforced magnesium substrate 1 are connected by bonding, and a connecting layer 4 is arranged between the two to achieve a stable connection. Optionally, the connecting layer 4 is a polyurethane adhesive. The wood board layer 2 and the reinforced magnesium substrate 1 are connected by a polyurethane adhesive and are cold-pressed at low temperature. Optionally, the connecting layer 4 covers the side of the reinforced magnesium substrate 1.
[0099] In one embodiment, the wear-resistant layer 3 is made of aluminum oxide surface paper impregnated with melamine resin, and other wear-resistant materials can also be used. When the wear-resistant layer 3 is directly connected to the wood board layer 2, it can be pressed at high temperature or cold-pressed at low temperature with an adhesive.
[0100] In one embodiment, if Figure 3 As shown, a decorative paper 5 is arranged between the wood board layer 2 and the wear-resistant layer 3. The decorative paper 5 and the wear-resistant layer 3 work together to improve the wear resistance of the composite board surface, reduce scratches and abrasion, and effectively improve the moisture resistance of the composite board. A layer of ink containing titanium dioxide is applied to the surface of the decorative paper 5, and then a melamine resin is applied to improve the scratch resistance. Optionally, the decorative paper 5 covers the side of the wood board layer 2.
[0101] In one embodiment, if Figure 4 As shown, a balancing paper 6 is arranged on the wood board layer 2 located on the inner side of the reinforced magnesium substrate 1, and the balancing paper 6 faces the proximal end of the ground or wall on which the composite board is laid. The balancing paper 6 can balance the stress of the board, stabilize the floor, prevent warping and deformation, so as to ensure the flatness of the floor. In addition, it can also effectively prevent moisture from penetrating from the back, thereby improving the moisture-proof performance of the composite board. The balancing paper 6 can be made of base paper impregnated with melamine resin, and after high temperature and high pressure treatment, it is pressed on the bottom layer of the composite board. Optionally, the balancing paper 6 covers the side of the wood board layer 2.
[0102] In one embodiment, if Figure 5As shown, the composite board also includes a cushion layer 7, which is an IXPE or EVA cushion layer 7. The cushion layer 7 is in contact with the ground or wall on which the composite board is laid, and improves the cushioning, heat insulation and moisture-proof capabilities of the composite board. The cushion layer 7 is connected to the wood board layer 2 by an adhesive or other means. When the balancing paper 6 is provided on the wood board layer 2 located on the inner side of the reinforced magnesium substrate 1, the cushion layer 7 is directly connected to the balancing paper 6.
[0103] The present application also relates to a method for manufacturing a composite plate with the reinforced magnesium substrate, which specifically comprises the following steps:
[0104] B1, taking a reinforced magnesium substrate 1 as the plate core of the composite plate;
[0105] B2, laying wooden board layers 2 on both sides of the reinforced magnesium substrate 1;
[0106] B3. Lay the wear-resistant layer 3 on the wooden board layer 2 located outside the reinforced magnesium base plate 1 in sequence.
[0107] Finally, it should be noted that the above are only some embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A reinforced magnesium substrate, characterized in that: The invention comprises the following components in parts by weight: 240-280 parts of magnesium oxide, 172-192 parts of wood fiber, 1.3-3.5 parts of citric acid, 1.3-3.5 parts of phosphoric acid, 1.3-3.5 parts of sodium sulfate, 90-120 parts of magnesium sulfate and 109-130 parts of water.
2. A reinforced magnesium substrate according to claim 1, characterized in that: The weight ratio of citric acid, phosphoric acid and sodium sulfate is 1:1:
1.
3. A reinforced magnesium substrate according to claim 1, characterized in that: The weight portion of the magnesium oxide is 255-265 parts; the weight portion of the magnesium sulfate is 100-110 parts; and the weight portion of the water is 115-125 parts.
4. A reinforced magnesium substrate according to claim 1, characterized in that: The fiber length of the wood fiber is 3-6 mm, and the moisture content of the wood fiber is 0.5%-10%.
5. The reinforced magnesium substrate according to claim 1, characterized in that: The magnesium oxide is light-burned magnesium oxide, and the magnesium sulfate is anhydrous magnesium sulfate.
6. A composite panel with a reinforced magnesium substrate as claimed in any one of claims 1 to 5, characterized in that: include: A reinforced magnesium substrate configured as a sheet core of the composite panel; The wooden board layer is arranged on both sides of the reinforced magnesium base plate and fixed relatively to the reinforced magnesium base plate; The wear-resistant layer is arranged on the wooden board layer located outside the reinforced magnesium base plate and is relatively fixed to the wooden board layer.
7. The composite board with the reinforced magnesium substrate according to claim 6, characterized in that: The composite board further comprises a connection layer, wherein the connection layer is arranged between the wood board layer and the reinforced magnesium substrate, and the connection layer is a polyurethane adhesive.
8. The composite board with the reinforced magnesium substrate according to claim 6, characterized in that: The composite board further comprises decorative paper, which is arranged between the wood board layer and the wear-resistant layer.
9. The composite board with the reinforced magnesium substrate according to claim 6, characterized in that: The composite board also includes balancing paper, which is arranged on the wood board layer located on the inner side of the reinforced magnesium base plate, and faces the proximal end of the ground or wall on which the composite board is laid.
10. The composite board with the reinforced magnesium substrate according to claim 6, characterized in that: The composite board further comprises a cushion layer, which is in contact with the ground or wall surface on which the composite board is laid.